Chiral carboxylic acid ligands derived from camphoric acid - Moloney, M; Paul, DR; Thompson, R; Wright, E (1996)
Versatile and convenient preparations of chiral carboxylic acid ligands, derived from camphoric acid, are described, either by esterification of camphoric dichloride or by a regioselective opening of the corresponding anhydride by a variety of alcohols or diols.